Personnel Service (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1952)
THE following employment items are made available to AIME members on a nonprofit basis by the Engineering Societies Personnel Service, Inc., operating in cooperation with the Four Founder Societies. Local offices of the Personnel Service are at 8 W. 40th St., New York 18; 100 Farnsworth Ave., Detroit; 57 Post St., Son Francisco; 84 E. Randolph St., Chicago 1. Applicants should address all mail to the proper key numbers in care of the New York office and include 6c in stomps for forwarding and returning application. The applicant agrees, if placed in a position by means of the Service, to pay the placement fee listed by the Service. AIME members may secure a weekly bulletin of positions available for $3.50 a quarter, $12 a year. MEN AVAILABLE Sales Engineer, 37, seven years experience Europe and Latin America both in underground work and administrative and sales work; speaks fluent Spanish, Portuguese, French. Desires responsible position preferably export in U. S. M-692. Superintendent, 46, married. Experience covers mining and metallurgy as mining engineer and as general superintendent; metallurgy of leaching, flotation, cyanidation; development, construction, operation. Presently available. Prefer U.S.A. M-693-333-E-1-San Francisco. Mine Manager, Superintendent, Consultant, 61, married. Design and erection of mining and mill plants-examinations. Many years as superintendent, manager, consultant, designer and builder of mining plants, flotation mills, concentration mills. Available one month's notice. Prefer U. S. but foreign acceptable if good climate. M-695-4211-E-9-San Francisco.